Detection of loci associated with water-soluble carbohydrate accumulation and environmental adaptation in white clover (Trifolium repens L.) : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Biology at Massey University, Palmerston North, New Zealand - Pearson, Sofie (Massey University, 2021)
White clover (Trifolium repens L.) is an economically important forage legume in New Zealand/Aotearoa (NZ). It provides quality forage and a source of bioavailable nitrogen fixed through symbiosis with soil Rhizobium bacteria. This thesis investigated the genetic basis of two traits of significant agronomic interest in white clover. These were foliar water-soluble carbohydrate (WSC) accumulation and soil moisture deficit (SMD) tolerance. Previously generated divergent WSC lines of white clover were characterised for foliar WSC and leaf size. Significant (p < 0.05) divergence in foliar WSC content was observed between five breeding pools. Little correlation was observed between WSC and leaf size, indicating that breeding for increased WSC content could be achieved in large and small leaf size classes of white clover in as few as 2 – 3 generations. Genotyping by sequencing (GBS) data were obtained for 1,113 white clover individuals (approximately 47 individuals from each of 24 populations). Population structure was assessed using discriminant analysis of principal components (DAPC) and individuals were assigned to 11 genetic clusters. Divergent selection created a structure that differentiated high and low WSC populations. Outlier detection methodologies using PCAdapt, BayeScan and KGD-FST applied to the GBS data identified 33 SNPs in diverse gene families that discriminated high and low WSC populations. One SNP associated with the starch biosynthesis gene, glgC was identified in a genome-wide association study (GWAS) of 605 white clover individuals. Transcriptome and proteome analyses also provided evidence to suggest that high WSC levels in different breeding pools were achieved through sorting of allelic variants of carbohydrate metabolism pathway genes. Transcriptome and proteome analyses suggested 14 gene models from seven carbohydrate gene families (glgC, WAXY, glgA, glgB, BAM, AMY and ISA3) had responded to artificial selection. Patterns of SNP variation in the AMY, glgC and WAXY gene families separated low and high WSC individuals. Allelic variants in these gene families represent potential targets for assisted breeding of high WSC levels. Overall, multiple lines of evidence corroborate the importance of glgC for increasing foliar WSC accumulation in white clover. Soil moisture deficit (SMD) tolerance was investigated in naturalised populations of white clover collected from 17 sites representing contrasting SMD across the South Island/Te Waipounamu of NZ. Weak genetic differentiation of populations was detected in analyses of GBS data, with three genetic clusters identified by ADMIXTURE. Outlier detection and environmental association analyses identified 64 SNPs significantly (p < 0.05) associated with environmental variation. Mapping of these SNPs to the white clover reference genome, together with gene ontology analyses, suggested some SNPs were associated with genes involved in carbohydrate metabolism and root morphology. A common set of allelic variants in a subset of the populations from high SMD environments may also identify targets for selective breeding, but this variation needs further investigation.
Keywords: White clover; New Zealand; Genetics; Adaptation; Crop improvement; ADMIXTURE; BayeScan; BayeScEnv; discriminant analysis of principal components; environmental association analysis; genome-wide association study; genomics; genotyping by sequencing; KGD-FST; leaf area; local adaptation; OutFLANK; outlier detection; PCAdapt; phenotyping; population genetics; proteomics; selection; signatures of selection; single nucleotide polymorphism; soil moisture deficit; transcriptomics; Trifolium; water-soluble carbohydrate; 310803 Plant cell and molecular biology